2017
DOI: 10.4251/wjgo.v9.i4.184
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylorirecurrence after eradication in Latin America: Implications for gastric cancer prevention

Abstract: AIMTo estimate Helicobacter pylori (H. pylori) recurrence rate in Latin America, a region with a significant H. pylori prevalence and gastric cancer burden.METHODSPubMed, LILACS, SciELO, Cochrane databases and abstracts from relevant meetings were reviewed. Information collected included: Participants’ characteristics, recruitment strategy, diagnostic modality, treatment arms, follow-up and recurrence rates. Recurrence was calculated using 100-patients-year rates, and data were pooled using a random effects mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In Latin America, after initial treatment, a mean eradication rate of 72.2% (ranging from 30.2% to 100%) has been observed. In Brazil, the eradication success rate ranges from 60.4% to 100% [ 30 ]. It should, however, be pointed out that the eradication rate has decreased over time to below 80%, due mainly to multiple antibiotic resistance and patient compliance [ 12 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America, after initial treatment, a mean eradication rate of 72.2% (ranging from 30.2% to 100%) has been observed. In Brazil, the eradication success rate ranges from 60.4% to 100% [ 30 ]. It should, however, be pointed out that the eradication rate has decreased over time to below 80%, due mainly to multiple antibiotic resistance and patient compliance [ 12 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…These treatment protocols achieve eradication rates ∼90% [10]. To prevent progression of premalignant histological changes (such as atrophic gastritis and intestinal metaplasia) and recurrent peptic ulcer diseases, it is important to maintain H. pylori eradication status after successful treatment [11]. However, a negative result of a follow-up test after H. pylori treatment does not guarantee subsequent persistent eradication status in the future, even with the most effective treatment regimen currently available [12].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of identical genotypes at different times indicates treatment failure: the bacterium was suppressed but not eradicated. Xia et al [32] reported the unsuitability of certain antimicrobial therapies for H. pylori because they do not completely eradicate infection, thus resulting in recurrence. The presence of antibiotic-resistant strains is one of the most frequent causes of recurrent H. pylori infection; in this situation, selection pressure is exerted, resulting in the death of sensitive strains and the persistence of resistant strains.…”
Section: Discussionmentioning
confidence: 99%